Zombie theory: a reader - Lauro, Sarah Juliet (University of Minnesota Press, 2017)
Zombies first shuffled across movie screens in 1932 in the low-budget Hollywood film White Zombie and were reimagined as undead flesh-eaters in George A. Romero's The Night of the Living Dead almost four decades later. Today, zombies are omnipresent in global popular culture, from video games and top-rated cable shows in the United States to comic books and other visual art forms to low-budget films from Cuba and the Philippines. The zombie's ability to embody a variety of cultural anxieties–ecological disaster, social and economic collapse, political extremism–has ensured its continued relevance and legibility, and has precipitated an unprecedented deluge of international scholarship. Zombie studies manifested across academic disciplines in the humanities but also beyond, spreading into sociology, economics, computer science, mathematics, and even epidemiology. Zombie Theory collects the best interdisciplinary zombie scholarship from around the world. Essays portray the zombie not as a singular cultural figure or myth but show how the undead represent larger issues: the belief in an afterlife, fears of contagion and technology, the effect of capitalism and commodification, racial exclusion and oppression, dehumanization. As presented here, zombies are not simple metaphors; rather, they emerge as a critical mode for theoretical work. With its diverse disciplinary and methodological approaches, Zombie Theory thinks through what the walking undead reveal about our relationships to the world and to each other.
Keywords: 2-Histoire/Historiographie critique; 2-Étude des représentations; 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

The Transatlantic Zombie: Slavery, Rebellion, and Living Death - Lauro, Sarah Juliet. (Rutgers University Press, 2015)
Our most modern monster and perhaps our most American, the zombie that is so prevalent in popular culture today has its roots in African soul capture mythologies. The Transatlantic Zombie provides a more complete history of the zombie than has ever been told, explaining how the myth's migration to the New World was facilitated by the transatlantic slave trade, and reveals the real-world import of storytelling, reminding us of the power of myths and mythmaking, and the high stakes of appropriation and homage. Beginning with an account of a probable ancestor of the zombie found in the Kongolese and Angolan regions of seventeenth-century Africa and ending with a description of the way, in contemporary culture, new media are used to facilitate zombie-themed events, Sarah Juliet Lauro plots the zombie's cultural significance through Caribbean literature, Haitian folklore, and American literature, film, and the visual arts. The zombie entered US consciousness through the American occupation of Haiti, the site of an eighteenth-century slave rebellion that became a war for independence, thus making the figuration of living death inseparable from its resonances with both slavery and rebellion. Lauro bridges African mythology and US mainstream culture by articulating the ethical complications of the zombie's invocation as a cultural conquest that was rebranded for the American cinema. As The Transatlantic Zombie shows, the zombie is not merely a bogeyman representing the ills of modern society, but a battleground over which a cultural war has been fought between the imperial urge to absorb exotic, threatening elements, and the originary, Afro-disaporic culture's preservation through a strategy of mythic combat
Keywords: 2-Histoire/Historiographie critique; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Lyrical Nationalism: Gender, Friendship, and Excess in 1970s Hindi Cinema - Jha, Priya (The Velvet Light Trap, 2003)
In this essay I examine one particular feature of the films, the song-and-dance sequences, as they draw attention to the fractious nature of the postcolonial nation while simultaneously attempting to construct a space for the articulation of a consolidated national identity.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Contemporary Sino-Japanese Relations on Screen: A History, 1989-2005 - Kirsch, Griseldis (Bloomsbury Publishing, 2015)
Japan and China look back on a history of friendship as well as friction, particularly in recent decades. As the People's Republic of China's economy began to grow in the 1990s, so did its political weight within Asia and its economical relevance for Japan. Covering the years from 1989 to 2005, this book looks at Sino-Japanese relations through film and television drama in the crucial time of China's ascent to an economic superpower in opposition to Japan's own ailing economy. It provides an overview of how Japan views China through its visual media, offers explanations as to how oppositions between the two countries came to exist, and how and why certain myths about China have been conveyed.Griseldis Kirsch argues that the influence of visual media within society cannot be underestimated, nor should their value be lessened by them being perceived as part of 'popular culture'. Drawing on examples from a crucial 16 years in the history of post-war Japan and China, she explores to what extent these media were influenced by the political discourse of their time. In doing so, she adds another layer to the on-going debate on Sino-Japanese relations, bringing together disciplines such as media studies, history and area studies and thus filling a gap in existing research.
Google-Books-ID: gdqxCAAAQBAJ
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma